Development of a New Rubber Buckling-Restrained Brace System for Structures - Nima Ostovar; Farzad Hejazi (Applied Sciences)
Buckling-Restrained Braces (BRBs) are widely utilized in structures as an anti-seismic system to enhance performance against lateral excitations. While BRBs are designed to yield symmetrically under both tension and compression without significant buckling, their effectiveness is often limited to moderate seismic events. During high-intensity earthquakes, repetitive yielding can lead to core failure, resulting in the loss of BRB functionality and potentially causing structural collapse. This study proposes an innovative design for BRBs to improve energy dissipation capacity under severe seismic activity. The new design incorporates Ultra-High-Performance Fiber-Reinforced Concrete (UHPFRC) filler and hyper-elastic rubber components as primary load-bearing elements. Through extensive testing and simulation, the proposed Rubber Buckling-Restrained Brace (RBRB) was developed and manufactured by integrating hyper-elastic rubber between the concrete and core to enhance the device’s strength. Additionally, a prototype of the conventional BRB device was fabricated to serve as a benchmark for evaluating the performance of the RBRB. Experimental testing of both the conventional BRB and the proposed RBRB prototypes was conducted using a heavy-duty dynamic actuator to assess the RBRB’s performance under applied loads. Based on the experimental results, an analytical model of the proposed RBRB was formulated for use in finite element modeling and analysis. Furthermore, a specialized seismic design procedure for structures equipped with the RBRB was developed, according to the performance-based design method. This procedure was applied to the design of a seven-story steel structure, and the impact of the RBRB on the seismic response of the structure was investigated through finite element simulations. The analysis results demonstrated that the RBRB significantly improves the loading capacity and energy dissipation capabilities of structures, thereby enhancing their overall performance against earthquake excitations.